Coffee consumption and plasma biomarkers of metabolic and inflammatory pathways in US health professionals. Issue 3 (5th March 2019) - Hang, Dong; Kværner, Ane Sørlie; Ma, Wenjie; Hu, Yang; Tabung, Fred K; Nan, Hongmei; Hu, Zhibin; Shen, Hongbing; Mucci, Lorelei A; Chan, Andrew T; Giovannucci, Edward L; Song, Mingyang
ABSTRACT: Background: Coffee consumption has been linked to lower risk of various health outcomes. However, the biological pathways mediating the associations remain poorly understood. Objectives: The aim of this study was to assess the association between coffee consumption and concentrations of plasma biomarkers in key metabolic and inflammatory pathways underlying common chronic diseases. Methods: We investigated the associations of total, caffeinated, and decaffeinated coffee consumption with 14 plasma biomarkers, including C-peptide, insulin-like growth factor 1 (IGF-1), IGF binding protein (IGFBP) 1, IGFBP-3, estrone, total and free estradiol, total and free testosterone, sex hormone–binding globulin (SHBG), total adiponectin, high-molecular-weight (HMW) adiponectin, leptin, C-reactive protein (CRP), interleukin 6 (IL-6), and soluble tumor necrosis factor receptor 2 (sTNFR-2). Data were derived from 2 cohorts of 15, 551 women (Nurses' Health Study) and 7397 men (Health Professionals Follow-Up Study), who provided detailed dietary data before blood draw and were free of diabetes, cardiovascular disease, or cancer at the time of blood draw. Multivariable linear regression was used to calculate the percentage difference of biomarker concentrations comparing coffee drinkers with nondrinkers, after adjusting for a variety of demographic, clinical, and lifestyle factors. Results: Compared with nondrinkers, participants who drank ≥4 cups of total coffee/d had lower concentrations of C-peptide (−8.7%), IGFBP-3 (−2.2%), estrone (−6.4%), total estradiol (−5.7%), free estradiol (−8.1%), leptin (−6.4%), CRP (−16.6%), IL-6 (−8.1%), and sTNFR-2 (−5.8%) and higher concentrations of SHBG (5.0%), total testosterone (7.3% in women and 5.3% in men), total adiponectin (9.3%), and HMW adiponectin (17.2%). The results were largely similar for caffeinated and decaffeinated coffee. Conclusion: Our data indicate that coffee consumption is associated with favorable profiles of numerous biomarkers in key metabolic and inflammatory pathways. This trial was registered at clinicaltrials.gov as NCT03419455.